(Na(B.(Nn(B.(NsEROW (B:(NpOPULQRNAQ MONOGRAFIQs (NMONOGRAFIQs - (Na(B.(Nm(B.(NsTUPEL_s ((NlENINGRADs (NmUZYKAs, 1981)
(Nw KNIGA RASSKAZYWAETSQ O VIZNI I DEQTEL_NOSTI a(B.(Nn(B.(NsEROWA(B(1820-1871).s
Keywords: (NMONOGRAFIQs